PENGARUH PENAGIHAN PAJAK TERHADAP PENCAIRAN TUNGGAKAN PAJAK DI KPP DENPASAR BARAT - Nyoman Sentosa Hardika; Ni Luh Putu Ratih Sri Rahayu (Sekolah Tinggi Ilmu Ekonomi AMM, 2016)
One way to disburse tax arrears was with the activities of tax collection. Tax collection aims to make the Taxpayer pay off the tax debts. It is due to the activity of tax collection has forceful law power. Activity of tax collection carried out by the Tax Confiscator. This studyaimed to determine the effect of tax collection by the letter of reprimand, forced letter, and a warrant for the seizure of the disbursement of tax arrears. This study uses multiple regression analysis. The aims of the study are to determine the effect of active collection action against liquefaction tax arrears in KPP Denpasar Barat. The result of this study showed that simultaneous, active collection action significantly influence the disbursement of tax arrears. While partially, a letter of reprimand and forced letter and warrant significant influence in the seizure did not significantly affect the disbursement of tax arrears. Active collection action with a letter of reprimand, forced letter, and the seizure warrants are factors that determine the level of disbursement of tax arrears